Increasing food sustainability by utilization of biowaste to grow mealworms and their nutrient profile as human food - Nariman Ktil; Ida Holásková; Yong-Lak Park; Cangliang Shen; Kristen E. Matak; Jacek Jaczynski (Future Foods)
Yellow mealworm is explored globally as sustainable food, creating a need to optimize its nutritional composition. This study investigated effects of supplementing mealworm feed with biowaste, apple pomace. Growth performance including survival/pupation rates, nutrient composition of larvae/pupae, and total antioxidant capacity of oil extracted from mealworms were examined. Apple pomace-supplemented diet (AD) did not (P ≥ 0.05) affect growth performance compared to control diet (CD). Larvae survival rates were higher (P < 0.05) for CD than AD, although realistically negligible. Pupation rate was higher (P < 0.05) for CD. Importantly, survival rates were similar (P ≥ 0.05) for the CD and AD. Feeding resulted in nutrient accumulation. Protein and fat contents increased (P < 0.05) to ≈40 g/100 g for each nutrient. Protein was generally higher in larvae than pupae and fat typically increased with AD. Mealworms, particularly larvae are dense source of animal protein and fat for isolation and extraction to develop human food. Oils extracted from pupae (hexane and chloroform:methanol generally) yielded higher antioxidant capacity than larvae. Antioxidants did not (P ≥ 0.05) have statistical significance likely because oils did not contain water-soluble antioxidants. Apple pomace showed improvement of mealworm nutritional profile and could be utilized in farming a sustainable and alternative food source.